Pengaruh Kualitas Produk Dan Harga Terhadap Keputusan Pembelian Pada Kedai Kopi Think Sukasari Tangerang - Wahyu Santoso; Rosa Lesmana (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This quantitative study was conducted to determine the effect of Product Quality and price on purchasing decisions at Think Coffee Shop Sukasari Tangerang. The population in this study were consumers of Think Coffee Shop as many as 10541 consumers. The sample was determined by probability sampling technique using the slovin formula with a sample size of 99 respondents. With a simple regression value of Y = 20.179 + 0.645 X1, the test correlation coefficient is 0.431, the determination coefficient is 18.6%, and the partial hypothesis value of Product Quality is obtained with a calculated T value greater than the T table (4.706> 1.984) with significance (0.000 <0.05). resulting in that purchasing decisions are influenced by the Product Quality factor. With a simple linear regression value of Y = 4.402 +0.73 X2, a test correlation coefficient value of 0.594, a determination coefficient value of 35.2%, and a partial hypothesis value of price obtained with a calculated T value greater than the T table (7.266>1.984) with significance (0.000 <0.05). resulting in that purchasing decisions are influenced by price factors. With a multiple linear regression value of Y = 14.215 + 0.144 (X1) + 0.497 (X2) + e, a test correlation coefficient value of 0.605, a determination coefficient value of 36.5%, and a simultaneous hypothesis test value, the calculated F value is greater than the F table (27.641>3.091) with significance (0.000 <0.05).